Islamic Religious Education Learning Strategy in Increasing Students' Knowledge and Quality About Islamic Religious Education at Muhammadiyah Middle School 57 Medan - Baeha, Puspita Sari; Harfiani, Rizka (Jurnal Pendidikan Islam, 2024)
This study discusses the strategies used to improve the knowledge and quality of Islamic Religious Education (PAI) learning at SMP Muhammadiyah 57 Medan. Islamic Religious Education plays a crucial role in the lives of humans. Religion serves as a guide in striving to achieve a meaningful, peaceful, and dignified life. Recognizing the vital role of religion in human life, religious values in every individual's life become a necessity that must be pursued through education, whether in the family, school, or community. Islamic Religious Education aims to shape students into individuals who are faithful and devoted to God Almighty and possess noble character. Noble character encompasses ethics, morality, and virtues as manifestations of religious education. Learning strategies play a significant role in determining the success of education and the holistic development of students. The strategy of teaching Islamic Religious Education greatly influences the learning process. The learning strategy applied by a teacher must be appropriate to the conditions and needs of the students. The environmental conditions and professionalism of teachers in Islamic education affect the strategies and models of Islamic learning applied to students. Without the right strategy, the learning process will not run effectively and efficiently. Therefore, teachers, at the forefront of education, play an essential role in the learning process.